Lignite Coal and Biochar Reduce Ammonia Emissions from Broiler Litter - Miles , Dana M.; Adeli, Ardeshir; Brooks, John P. (International Journal of Poultry Science, 2020)
Background and Objective: Ammonia volatilizes from broiler litter in the rearing facility, during storage and upon land application. The gaseous release of NH3 to the air decreases bird productivity, decreases fertilizer value of the litter and can impair natural resources including nearby land, water and air. A chamber, acid-trap study was conducted to determine the effect of lignite coal and biochar on NH3 volatilization from broiler litter. Materials and Methods: Two sizes of biochar were investigated separately and two methods of application were utilized in a total of six experiments. Lignite or biochar (at 10, 20, or 30% by weight) were mixed into or broadcast over broiler litter in 1 L containers. Air exiting each chamber was trapped in acid and the amount of NH3 captured was determined via titration intermittently for 21 days. Results: Method of application was not significant whether mixed or broadcast for 10 and 20% applications but both lignite and biochar reduced NH3 losses. At the 30% application rate, broadcasting reduced emissions most. Overall NH3 losses were reduced 47-91% by lignite, 18-42% by bedding size biochar and 29-58% by soil size biochar. Conclusion: Both materials can be added to broiler litter to reduce NH3 emissions in broiler facilities, during storage and when applying litter as fertilizer. Integrators would need to assess the effects on bird digestion of biochar or lignite before broadcasting inside broiler facilities. Beyond the benefits of healthier birds and protecting the environment, the potential benefit is that broiler growers and farmers can confidently enjoy the labor and cost savings of broadcasting versus mixing these additives with broiler litter.